PS02.177: EFFECT OF PREHABILITATION ON FITNESS IN PATIENTS UNDERGOING NEOADJUVANT TREATMENT AND OESOPHAGOGASTRIC CANCER SURGERY: A RANDOMISED CONTROLLED TRIAL. (14th September 2018) - Allen, Sophie; Brown, Vanessa; Prabhu, Pradeep; Rockall, Timothy; Preston, Shaun; Sultan, Javed
Abstract: Background: Neoadjuvant chemotherapy (NAC) and surgery improves 5-year survival in patients with locally-advanced oesophagogastric (OG) cancer. NAC reduces fitness as assessed by cardiopulmonary exercise (CPX) testing. We aim to demonstrate improvement in CPX test performance in patients undergoing a 15-week 'prehabilitation' programme during and after NAC, compared those receiving 'standard care'. Methods: A single-centre, parallel-arm randomised controlled trial was conducted in patients undergoing NAC for OG cancer. Patients were assigned to a 15-week prehabilitation programme comprising twice weekly supervised aerobic and resistance training, a thrice weekly home exercise plan, and 6 Medical Coaching sessions (Prehab), or standard care (Control). CPX was performed at baseline (before NAC; Test 1), 2 weeks following NAC completion (Test 2), and during the preoperative week (Test 3). The primary outcome (anaerobic threshold (AT)) is powered for 48 patients (24 per group). Secondary outcomes include peak oxygen uptake (pVO2 ) and work rate (WR). Results: Since December 2016, 46 patients have been recruited, with a 15% drop-out rate (7/46). All patients received NAC. To date, complete dataset is available for 27 subjects (Prehab n = 15; Control n = 12). Groups were matched for baseline demographics and AT/pVO2 /WR ( P  = ns). At baseline: Mean AT 13.3 ± 2.91ml/kg/min, pVO2 797.85 ± 168.04ml/min/m 2, and WR 148.63 ± 40.18watts. Effects of NAC (Tests 1 to 2) : All subjects had a mean decline in AT (Prehab -1.41ml/kg/min vs. Control -1.69 ml/kg/min) with no difference in WR decline (Prehab -9.87watts vs. Control -9.66watts; P  = 0.98). At Test 2, there was a trend towards pVO2 improvement with Prehab (+ 20.2ml/min/m 2 ) whereas pVO2 in Controls deteriorated (-81.98ml/min/m 2 ; P  = 0.06). Effects of NAC and 5-week 'recovery period' (Tests 1 to 3) : There was a tendency towards a smaller AT decrease from baseline with Prehab subjects (-0.6ml/kg/min) compared with Controls (-1.5ml/kg/min; P  = 0.30). Compared with Test 1, Prehab patients demonstrated a non-significant trend towards improvement in pVO2 (+ 20.2ml/min/m 2 ) and WR (+ 1.86watts) following a period of recovery. Controls observed a decrease in both parameters (pVO2 -16.48ml/min/m 2, WR -3.5watts). Conclusion: A prehabilitation programme is feasible during and after NAC. Interim analysis demonstrates a trend towards return of baseline pVO2 in patients receiving prehabilitation. Trial completion is warranted and the full dataset will be available by June 2018. Disclosure: All authors have declared no conflicts of interest.